Z historii wymowy wyrazu hala ‘pastwisko górskie’ - Cybulski, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
Polish word hala “mountain pasture” is generally derived from the Slovak hol’a, and this borrowing, combined with the introduction of pseudo-correct a, was supposed to be credited to Romantic literature, and precisely was the result of etymological experiments of Seweryn Goszczyński. The present paper demonstrates that the word hala, written exclusively with a and often with ll, is a quite frequent phenomenon in the texts of Księga państwa żywieckiego (“The Book of the Żywiec State”) from the year 1681. The pronunciation hala instead of hola may have been used at that time by literate inhabitants of the Beskidy Mountains, familiar with the standard of the literary language, although rather poorly, thus inclined to adjust to the tendency of hypercorrectness. The German typographic influence cannot be excluded.